2018
DOI: 10.1080/14756366.2018.1512596
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of novel fragments inhibiting O-acetylserine sulphhydrylase by combining scaffold hopping and ligand–based drug design

Abstract: Several bacteria rely on the reductive sulphur assimilation pathway, absent in mammals, to synthesise cysteine. Reduction of virulence and decrease in antibiotic resistance have already been associated with mutations on the genes that codify cysteine biosynthetic enzymes. Therefore, inhibition of cysteine biosynthesis has emerged as a promising strategy to find new potential agents for the treatment of bacterial infection. Following our previous efforts to explore OASS inhibition and to expand and diversify ou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 42 publications
(47 reference statements)
0
17
0
Order By: Relevance
“…Cysteine metabolism (i.e., de novo biosynthesis and degradation) [17], is intimately connected with many bacterial functions relevant to infection, such as resistance to oxidative stress and resistance to antibiotics [18,19,20,21,22], biofilm formation [23], and toxin activation [24,25]. For this reason, this metabolic pathway has received much attention in the last ten years as a potential target for the development of antibiotics or antibiotic enhancers [17,26,27,28,29,30,31,32,33,34,35,36,37,38]. Cysteine biosynthesis in bacteria is performed through eight enzymes plus several permeases [17] (Figure 1A) that allow entry of sulfate/thiosulfate inside the cell.…”
Section: Introductionmentioning
confidence: 99%
“…Cysteine metabolism (i.e., de novo biosynthesis and degradation) [17], is intimately connected with many bacterial functions relevant to infection, such as resistance to oxidative stress and resistance to antibiotics [18,19,20,21,22], biofilm formation [23], and toxin activation [24,25]. For this reason, this metabolic pathway has received much attention in the last ten years as a potential target for the development of antibiotics or antibiotic enhancers [17,26,27,28,29,30,31,32,33,34,35,36,37,38]. Cysteine biosynthesis in bacteria is performed through eight enzymes plus several permeases [17] (Figure 1A) that allow entry of sulfate/thiosulfate inside the cell.…”
Section: Introductionmentioning
confidence: 99%
“…In 2016, Pieroni et al [115,116], starting from the evidence that SAT competitively inhibits OASS-A, developed a rational design of the first sulfydrylase inhibitors based on the structural features of the OASS–SAT interaction. Taking into account the data from their previous studies [117], and combining computational [118,119] and spectroscopic approaches, such as saturation transfer difference (STD) and nuclear magnetic resonance (NMR), they rationally designed and synthesized a series of 2-phenylcyclopropane carboxylic acid derivatives tested against both isoforms of St -OASS [120]. Indeed, they demonstrated that the compounds binding to the enzyme active sites efficiently inhibit both OASS-A and B isoforms by competing with SAT.…”
Section: Targeting Antivirulence Factorsmentioning
confidence: 99%
“…Scaffold hopping is a powerful and promising strategy for drug discovery 34 . It has been extensively used for the design of structurally novel bioactive molecules [35][36][37][38] , which generally incorporates ring opening, ring closure, heterocycle replacement, and shape/topology-based scaffold hopping 39,40 . Herein, we applied the heterocycle replacement and shape-based scaffold hopping strategy towards PFI-1, a BRD inhibitor developed by Pfizer Worldwide R&D. First, we analysed the binding mode of PFI-1 binds to the BRD4 bromodomain.…”
Section: Design Of New Brd4 Inhibitors Containing a Coumarin Scaffoldmentioning
confidence: 99%